The Prospective Effect of Green Tea versus Pomegranate Peels Extracts on Submandibular Salivary Glands of Albino Rats after Methotrexate Administration (Histological and Immunohistochemical Study) - Rasha M. Taha; Ghada A. Abdel-Latif; Rania H. Said (International Journal of Dentistry)
Background. There is curiosity in the use of substances that can stop cell damage. Antioxidants are substances that can prevent free radicals from damaging cells, and they can be used to treat and avoid a wide variety of illnesses. Objectives. The current investigation set out to evaluate the histological changes brought on by a single high dose of methotrexate in the submandibular glands of rats treated with green tea and pomegranate peel extract, both are well-known as antioxidants. Materials and Methods. Forty-eight healthy Albino rats were used in the current study. Animals were divided into six groups. Group 1: Vehicle group which is control group, Group 2: methotrexate treated group, Group 3: green tea control group, Group 4: pomegranate peel extract control group, Group 5: green tea + methotrexate group, and Group 6: pomegranate peel extract + methotrexate group. Rats of all groups were left 1 week after the end of the treatment. Cervical dislocation was used to kill all of the rats. Samples were gained from the rats’ submandibular salivary glands of different groups for histological and immunohistochemical evaluation. Results. Green tea + methotrexate group showed improvement in the histological picture of the submandibular salivary gland compared to methotrexate group and the pomegranate peel extract + methotrexate group. Conclusion. The antioxidant activity of green tea is more potent than that of pomegranate peels extract in blocking methotrexate that induced cytotoxicity in the submandibular salivary glands of rats. As a result, it can be administered to people undergoing cancer treatment as a safeguard for their salivary glands.